Doctrine of the CJEU on the immunity of execution of international organizations and the field of application of the Brussels I bis Regulation - Pérez Martín, Lucas Andrés (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
In 2020 the CJEU has framed in two important resolutions the types of actions in which the legal business of states or international organizations with private lawpersons are included within the framework of the Brussels I bis Regulation under the domain of civil and commercial maters and are not covered by the principle of international law of immunity from jurisdiction and enforcement. In the present paper we analyze the Judgment of September 3, 2020, which resolves a procedure in which NATO alleged that the deposit contract to ensure the payments of a fuel supply contract to assist the operation carried out in Afghanistan after The 2001 attacks, were protected by the principle of immunity from execution, which the CJEU denied.
Keywords: immunity from jurisdiction; immunity from execution; civil and commercial matters; deposit agreement; provisional attachment